2022
DOI: 10.2147/oajc.s360408
|View full text |Cite
|
Sign up to set email alerts
|

Disruption in Essential Health Service Delivery: A Qualitative Study on Access to Family Planning Information and Service Utilization During the First Wave of COVID-19 Pandemic in Uganda

Abstract: Background Coronavirus disease 2019 (COVID-19) remains a challenge to public health with profound impact on people’s lives. With several mitigation measures implemented to curb the spread of COVID-19, these impacted on access and utilization of general health services including family planning (FP) services. The objective of the study was to understand the extent to which COVID-19 interrupted access and utilization of FP services as well as highlight the challenges faced during the lockdown in Uga… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
32
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 13 publications
(32 citation statements)
references
References 11 publications
0
32
0
Order By: Relevance
“…Overall, 14 studies reported data from four low-income countries ( 34–47 ), 21 studies were focused on 13 lower-middle income countries ( 48–68 ), seven studies were conducted in five upper-middle income countries ( 69–75 ) and three were multi-centred ( 76–78 ). Out of 45 included studies, 11 studies were cross-sectional ( 41 , 45 , 48 , 51 , 55–57 , 65 , 69 , 70 , 76 ), 14 were pre-post studies ( 34 , 38 , 49 , 50 , 52 , 53 , 56 , 62 , 64 , 72–75 , 77 ), nine were time-series ( 35 , 37 , 39 , 43 , 58 , 59 , 67 , 71 , 78 ), five were mixed methods ( 36 , 42 , 47 , 61 , 63 ) and six were qualitative ( 40 , 44 , 46 , 54 , 60 , 68 ). The included studies’ characteristics are summarised in Table 1 .…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…Overall, 14 studies reported data from four low-income countries ( 34–47 ), 21 studies were focused on 13 lower-middle income countries ( 48–68 ), seven studies were conducted in five upper-middle income countries ( 69–75 ) and three were multi-centred ( 76–78 ). Out of 45 included studies, 11 studies were cross-sectional ( 41 , 45 , 48 , 51 , 55–57 , 65 , 69 , 70 , 76 ), 14 were pre-post studies ( 34 , 38 , 49 , 50 , 52 , 53 , 56 , 62 , 64 , 72–75 , 77 ), nine were time-series ( 35 , 37 , 39 , 43 , 58 , 59 , 67 , 71 , 78 ), five were mixed methods ( 36 , 42 , 47 , 61 , 63 ) and six were qualitative ( 40 , 44 , 46 , 54 , 60 , 68 ). The included studies’ characteristics are summarised in Table 1 .…”
Section: Resultsmentioning
confidence: 99%
“…COVID-19 demonstrated rapid community transmission, resulting in widespread outbreaks across countries and continents. The exponential growth in cases has instilled fear of contagion in many individuals and communities ( 36 , 40 , 42 , 44 , 46 , 47 , 54 , 60 , 61 , 68 ). Participants shared that healthcare facilities were considered as potential sources of COVID-19 transmission ( 36 , 40 , 42 , 44 , 47 , 60 ); therefore, they tend to postpone or avoid general healthcare visits and antenatal care due to the “fear of acquiring the disease” ( 47 ).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…CBFP methods are an effective strategy to scaling up contraceptives in rural areas where structural barriers like geographic distance and long wait lines impede uptake, and Uganda has pledged to scale up CBFP as part of their FP2030 strategy [50]. Moreover, this approach may be important to explore in the context of COVID-19 outbreaks and related lockdowns preventing communities from receiving family planning from facilities [51]. However, CBFP efforts need to be paired with demand generation activities to optimize their effect, while also addressing the structural barriers identi ed in our study related to stock out and low health worker capacity to provide LARCs.…”
Section: Discussionmentioning
confidence: 99%
“…Although the impact of COVID was accounted for in the regression models, we still believe that overall impact of COVID-19 on the disruption of the provision of essential health services including maternal, neonatal and child health outcomes cannot be underestimated and the pandemic had the potential to affect the pattern of health coverage between 2020 and 2021 (23,24).…”
Section: Limitationsmentioning
confidence: 99%